Hunger in French Guiana's Vulnerable Urban Neighborhoods: A Neglected Consequence of COVID-19. Issue 1 (March 2023) - Basurko, Celia; Dupart, Ophélie; Savy, Mathilde; Obert-Marby, Camille; Mvogo, Alexandra; Gonzalez, Adriana; Trepont, Aude; Cann, Lisa; Boceno, Claire; Osei, Lindsay; Creton, Pierre-Marie; Dufit, Valentin; et al.
Background: In French Guiana, restrictions to control the spread of SARS-CoV-2 were put in place between March 2020 and March 2022. In vulnerable urban neighborhoods, during this period, requests for food assistance increased and fear of hunger overtook fear of being affected by COVID-19. Objective: The objective of this survey was to describe food security during the COVID-19 pandemic in French Guiana and to study the relationship between the socioeconomic conditions of the study households and household hunger. Methods: A multicenter survey was therefore conducted in mobile clinics and fixed structures providing care to at-risk urban populations. In a face-to-face interview, a community health worker asked participants questions about the sociodemographic and economic profile of the household, and about household food security (food consumption score, coping strategies in the face of food shortages, and household hunger index). Two hundred seventy-seven households were recruited in February 2021. Results: According to the household hunger scale, 42.6% of households experienced moderate hunger and 23.8% of households experienced severe hunger in the month preceding the survey. Lack of residence permit, lack of social support, water insecurity, small housing, and lack of access to an urban garden were determinants related to the risk of household hunger. Conclusions: Food insecurity has affected a large majority of the households in this survey, and the immediate consequences for children's health were already apparent. These results draw attention to a neglected health problem in a socioeconomically vulnerable population during the COVID-19 pandemic.